2019
DOI: 10.1021/acs.est.9b03649
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite-Mediated Photooxidation of Vanillin in the Atmospheric Aqueous Phase

Abstract: Nitrite (NO 2 − ) and its conjugate acid, nitrous acid (HNO 2 ), have long been recognized as a ubiquitous atmospheric pollutant as well as an important photochemical source of hydroxyl radicals (•OH) and reactive nitrogen species (•NO, • NO 2 , •N 2 O 3 , etc.) in both the gas phase and aqueous phase. Although NO 2 − /HNO 2 plays an important role in atmospheric chemistry, our understanding on its role in the chemical evolution of organic components in atmospheric waters is rather incomplete and is still in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 85 publications
6
100
0
Order By: Relevance
“…IPA can be classified as both a biogenic (from grass, Olofsson et al, 2003) and anthropogenic VOC (e.g., from solvents and industrial processes, Hippelein, 2004;Lewis et al, 2020), while bicarbonate is an inorganic anion observed in fog water from both urban and rural locations (Collett et al, 1999;Straub et al, 2012;Straub, 2017). IPA and NaBC are particularly interesting also because they can produce other radicals (e.g., • HO2 and carbonate radical, CO3 • ) that may react with nitrate photolysis products Wang et al, 2021) and they can act as • OH scavengers (Warneck and Wurzinger, 1988;Gen et al, 2019b;Pang et al, 2019a), although it must be noted that these compounds were not added in excess for our experiments. Moreover, comparisons were made between the photooxidation of guaiacol (0.1 mM), a non-carbonyl phenol, in the presence of VL (0.1 mM) or AN (1 mM).…”
Section: Aqueous Phase Photo-oxidation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPA can be classified as both a biogenic (from grass, Olofsson et al, 2003) and anthropogenic VOC (e.g., from solvents and industrial processes, Hippelein, 2004;Lewis et al, 2020), while bicarbonate is an inorganic anion observed in fog water from both urban and rural locations (Collett et al, 1999;Straub et al, 2012;Straub, 2017). IPA and NaBC are particularly interesting also because they can produce other radicals (e.g., • HO2 and carbonate radical, CO3 • ) that may react with nitrate photolysis products Wang et al, 2021) and they can act as • OH scavengers (Warneck and Wurzinger, 1988;Gen et al, 2019b;Pang et al, 2019a), although it must be noted that these compounds were not added in excess for our experiments. Moreover, comparisons were made between the photooxidation of guaiacol (0.1 mM), a non-carbonyl phenol, in the presence of VL (0.1 mM) or AN (1 mM).…”
Section: Aqueous Phase Photo-oxidation Experimentsmentioning
confidence: 99%
“…CC BY 4.0 License. constant of 4.56 × 10 5 M atm -1 ; Yaws, 1994), a model compound for methoxyphenols which are abundant in BB emissions (Pang et al, 2019a), which has been shown to yield low-volatility products (Li et al, 2014) via aqueous • OH oxidation and direct photodegradation. Photodegradation kinetics and aqSOA yields have been reported for direct VL photodegradation (Smith et al, 2016), with oxygenated aliphatic-like compounds (high H:C, ≥1.5 and low O:C, ≤0.5 ratios) reported as the most likely products (Loisel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenols react with nitrogen dioxide, nitrous acid, and nitrate radicals -oxidants that are abundant in urban downwind areas due to intense NO x emissions. These reactions produce nitrophenols which are of concern for their toxicity and light absorbing properties (Pang et al 2019;Yuan et al 2016;Zhang et al 2016). BBOA also includes nitroaromatics, dioxins (e.g., polychlorinated dibenzo-p-dioxins, polychlorinated dibenzofurans, and polychlorinated biphenyls), and polycyclic aromatic hydrocarbons (PAHs) (Fleming et al 2020;Samburova et al 2016;Zhang, Buekens, and Li 2017).…”
Section: Organic Composition Of Biomass Burning Aerosols-qi Zhangmentioning
confidence: 99%
“…Biogenic SOC (12.4 %) and biomass burning SOC (12.3 %) contributed comparable proportions to total WSOC, and both contributed more to the hydrophobic fraction. Biomass burning SOC, which is mainly formed from the phenolic compounds, has been widely recognized to contribute notably to the water-soluble brown carbon (HULISWS) (Smith et al, 2016;Pang et al, 2020). Biogenic SOC in the hydrophilic fraction (contribution ratio of aged to fresh: 1.44) was more aged than that in the hydrophobic fraction (contribution ratio of aged to fresh: 0.54), because the atmospheric aging processes would generally increase the polarity of organic aerosols (Baduel et al, 2011;Guo et al, 2014).…”
Section: Source Apportionment Of Wsocmentioning
confidence: 99%